Anderson Hall
Originally named "Boys Dormitory" or "Dormitory #1", this was one of the first two buildings built at Cal Poly, designed by William H. Weeks. Possibly in the 1909-1911 time period it housed women students. By the 1920s the building was named "Science Hall." Later it was renamed "Anderson Hall." It was demolished in 1941.